Immunodetection of Helicobacter sp. and the associated expression of ABO blood group antigens in the gastric mucosa of captive and free-living New World primates in the Amazon region - AGUIAR, Délia Cristina Figueira (2014)
The histo-blood group ABH antigens were first described in humans. These antigens are only present on erythrocytes from great apes and humans, while in more primitive animals they are found in tissues and body fluids. The ABH antigens are mainly distributed in tissues exposed to the external environment and potentially serve as ligands for pathogens or inhibitors of tissue connections. The objective of this paper was two-fold: (i) to determine the presence of Helicobacter sp. in the gastric mucosa of 16 captive and 24 free-living New World monkeys and (ii) to evaluate the presence of histopathological alterations related to bacterial infection and the associated expression of ABH antigens in the tissue. Stomach tissues from 13 species of monkey were assessed using haematoxylin-eosin and modified Gram staining (Hucker) methods. An immunohistochemical analysis of the tissue revealed the presence of infectious bacteria that were characteristic of the genus Helicobacter sp. The results demonstrate that various species of monkey might be naturally infected with the Helicobacter sp. and that there is an increased susceptibility to infection. This study serves as a comparative analysis of infection between human and non-human primates and indicates the presence of a new species of Helicobacter.